Cultural Expertise, Law, and Rights : A Comprehensive Guide. - Holden, Livia. (Taylor & Francis Group, 2023)
This book introduces readers to the theory and practice of cultural expertise in the resolution of conflicts and the claim of rights in diverse societies and cross-cultural disputes.